2017
DOI: 10.3390/hydrology4030043
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Stream Water Nitrate Concentrations between a Nitrogen-Saturated Upland Forest and a Downstream Mixed Land Use River Basin

Abstract: Nitrogen (N) saturation of upland forests has been assumed to be a substantial N source downstream. However, removal processes of N, including assimilation and denitrification in the downstream area, have not been clarified. To evaluate the N removal processes, nitrate and organic N concentrations, as well as nitrogen isotope ratio (δ 15 N) and oxygen isotope ratio (δ 18 O) of NO 3 − were measured along three rivers of Tatara River Basin, Japan where upland forests have already been N-saturated. Geographic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…If the precipitation was around 10 mm day −1 , we collected samples after checking the situation of each stream the next day, whether the water level was not lowered (judge based on the wetness of stones in the stream) and the water was not muddy. To learn the spatial distribution of stream chemistries, stream waters are investigated at baseflow condition sometimes (e.g., Konohira et al, 2006; Nishina et al, 2017; Shinozuka et al, 2017). All water samples were transported in the cooler box with frozen refrigerants and stored in the refrigerator at 6°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…If the precipitation was around 10 mm day −1 , we collected samples after checking the situation of each stream the next day, whether the water level was not lowered (judge based on the wetness of stones in the stream) and the water was not muddy. To learn the spatial distribution of stream chemistries, stream waters are investigated at baseflow condition sometimes (e.g., Konohira et al, 2006; Nishina et al, 2017; Shinozuka et al, 2017). All water samples were transported in the cooler box with frozen refrigerants and stored in the refrigerator at 6°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…S1 ). In this region, high levels of NO 3 − leaching from headwater streams are observed 8 , 9 . The mean annual temperature and precipitation are 15.9 °C and 1769 mm over the last 10 years, respectively 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Chronic high N deposition has strongly influenced N cycling and may potentially cause N saturation in forested ecosystems, leading to high levels of N leaching from these ecosystems 2 . Extensive studies in Europe 3 , China 4 , North America 5 , and Japan 6 , 7 have shown the major role of atmospheric deposition on elevated nitrate (NO 3 − ) concentrations in stream water from forest ecosystems, contributing to downstream eutrophication 8 , 9 .…”
mentioning
confidence: 99%
“…Results (figure 10) appeared that concentrations of nitrate and nitrite were above Iraqi standard limiting of drinking water, also, showed a significant differentiation among seasons and among sites, with positive correlation coefficient with temperature and TDS (r=0.99, 0.75) respectively. The high concentrations of NO2 and NO3 could be return to position of stream that passed through agricultural and urban areas [49] with higher possibility to reach fertilizers and nitrogen wastes to the water stream [50].…”
Section: -2-chemical Parametersmentioning
confidence: 99%